Using a heuristic multi-objective genetic algorithm to solve the storage assignment problem for CPS-based pick-and-pass system. Issue 9 (21st October 2021) - Tu, Mengru; Yang, Ming-Feng; Kao, Sheng-Long; Lin, Feng-Cheng; Wu, Ming-Hung; Lin, Cheng-Kuan
ABSTRACT: With the advancement of AI and the widespread application of IoT and cloud computing, the pick-and-pass system (PKPS) can potentially be transformed into a cyber-physical system (CPS) based intelligent warehouse picking system. This paper proposes a CPS-based PKPS with a heuristic multi-objective genetic algorithm to solve the NP-hard storage assignment problem (SAP) for order picking operations in an e-commerce-based warehouse. The proposed algorithm considers both the workload balance between picking lines and emergency replenishment during picking operation. Finally, the study shows that the proposed algorithm is effective in improving the efficiency of picking operations based on software simulation.